Genotype Is Associated to the Degree of Virilization in Patients With Classic Congenital Adrenal Hyperplasia - Neocleous, Vassos; Fanis, Pavlos; Phylactou, Leonidas A.; Skordis, Nicos (Frontiers in Endocrinology, 2018)
Background: Molecular defects of CYP21A2 consistently decrease 21-hydroxylase activity and result in a variable expression of disease severity in patients with congenital adrenal hyperplasia (CAH). Aim: The genotype and biochemical findings were examined in an attempt to reveal any association to the degree of virilization in classic CAH patients. Methods: The study included 18 CAH patients with complete characterization of CYP21A2 mutations and were sorted based on the severity of the inherited mutations and the expected % of 21-hydroxylase enzyme activity. Results: Eleven out of the 18 patients manifested the SW form with the remaining 7 to exhibit the SV form. The most frequent genetic defect in the classic salt-wasting (SW) and simple virilising (SV) forms was the IVS2-13A/C>G (36.1%) mutation, followed by delEX1-3 (19.4%) and p.Ile172Asn (19.4%). Four patients, who shared a combination of 2 mutations belonging to the most severe type, manifested only the SW form. Four out of 5 patients who shared in homozygosity the IVS2-13A/C>G mutation demonstrated the SW form and only one the SV form. All four patients who shared the p.Ile172Asn mutation either in homozygous or compound heterozygous state manifested the SV form. Interestingly, a female neonate with SW bearing the IVS2-13A/C>G/Large del exhibited complete male virilisation (Prader 5). The remaining four affected female new-borns also exhibited the SW form, with two of them virilised as Prader 3 and the other two as Prader 4. Virilisation with clitoromegaly was also observed in a female, who presented with premature adrenarche and carried the less severe p.Pro30Leu mutation. Conclusion: The frequency of the underlying mutations in our patients with the classic form of CAH is variable but quite similar with the ones reported in the Mediterranean region. Therefore, the identification of the severe CYP21A2 defects in Cypriot patients and their comparison with the incidence and severity in different populations will make a valuable diagnostic tool for genetic counselling in the classic form of CAH.